1998
DOI: 10.1002/(sici)1521-3951(199805)207:1<95::aid-pssb95>3.0.co;2-t
|View full text |Cite
|
Sign up to set email alerts
|

Electron-Phonon Interaction and Phase Transitions in [C2H5NH3]2CuCl4 Crystals

Abstract: Optical and spectral investigations confirmed the availability of phase transitions in [C 2 H 5 NH 3 ] 2 CuCl 4 at T 1 = 364 K, T h 2 = 356 K, T 3 = 232 K. It has been found that the empirical Urbach rule is fulfilled in all phases. It is shown, that in the high-temperature phases skeletal vibrations of the C±N±C group interact with phonons, whereas in the low-temperature phases internal vibrations of the metal±halogen complex occur. A ferroelastic domain structure was observed using the polarising microscope … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

1999
1999
2020
2020

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 5 publications
1
13
0
Order By: Relevance
“…Following optical and spectral investigations confirmed availability of the phase transitions in EA-CuCl 4 at T1 = 364 K, TI = 356 K, T4 = 232 K [3,4], although it was supposed that anomalous behaviour of investigated spectral properties observed both at heating and cooling around the temperature of T = 330 K should be related to earlier unknown phase transition [4]. Such an ambiguity demands further study of the high temperature phase transitions using more precise methods.…”
Section: Introductionmentioning
confidence: 99%
“…Following optical and spectral investigations confirmed availability of the phase transitions in EA-CuCl 4 at T1 = 364 K, TI = 356 K, T4 = 232 K [3,4], although it was supposed that anomalous behaviour of investigated spectral properties observed both at heating and cooling around the temperature of T = 330 K should be related to earlier unknown phase transition [4]. Such an ambiguity demands further study of the high temperature phase transitions using more precise methods.…”
Section: Introductionmentioning
confidence: 99%
“…The IR absorption bands at room tem- perature were identified in a previous paper [17]. Nevertheless, some additional information would be obtained from the analysis of their temperature evolution (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Taking into account that the temperature evolution of the absorption bands, which correspond to the internal transitions of Cu 2 ion and lie below 2 eV, has been investigated fairly well [9], it would be convenient to analyse the behaviour of the absorption edge observed within the energy region 2.5 to 4 eV depending on the polarization of light. One can suggest that the most intensive low energy CT band I in EA-CuCl 4 should be observed when the light is polarized along the directions of the shortest bonds ªligand±metalº in the equatorial plane, namely along [110] and [1 " 10].…”
Section: Resultsmentioning
confidence: 99%
“…it was suggested that the absorption bands observed within the framework of 1.5 to 2.0 eV are characteristic of the distorted octahedral coordination of the copper ion [9].…”
Section: Introductionmentioning
confidence: 83%
See 1 more Smart Citation